2023
DOI: 10.1186/s12889-022-14897-w
|View full text |Cite
|
Sign up to set email alerts
|

Mapping and analysis of laws influencing built environments for walking and cycling in Australia

Abstract: Background Physical inactivity is a significant public health concern, with limited signs of improvement despite a global commitment to achieving the World Health Organization’s target of 15% reduction by 2030. A systems approach is required to tackle this issue, involving the creation of environments that are conducive to physical activity. Laws represent an important tool for regulating the built environment for physical activity, are a mechanism for systems change, and have the capacity to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Previous research seeking to encourage movement through a systems-approach found similar leverage points (42,51). For example, systems representing recreational participation have likewise found the importance of goals (e.g., serving the needs of young people) and varying forms of structural change (e.g., urban design, safety, policy change to support movement, laws, regulation) (42,(51)(52)(53). These studies also underscore the importance of feedback loops and delays (e.g., appeal of facilities growing as more people use them) (42,(51)(52)(53), points in which the systems-consortium also recognised and discussed in regard to implementing a shared strategy.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Previous research seeking to encourage movement through a systems-approach found similar leverage points (42,51). For example, systems representing recreational participation have likewise found the importance of goals (e.g., serving the needs of young people) and varying forms of structural change (e.g., urban design, safety, policy change to support movement, laws, regulation) (42,(51)(52)(53). These studies also underscore the importance of feedback loops and delays (e.g., appeal of facilities growing as more people use them) (42,(51)(52)(53), points in which the systems-consortium also recognised and discussed in regard to implementing a shared strategy.…”
Section: Discussionmentioning
confidence: 87%
“…For example, systems representing recreational participation have likewise found the importance of goals (e.g., serving the needs of young people) and varying forms of structural change (e.g., urban design, safety, policy change to support movement, laws, regulation) (42,(51)(52)(53). These studies also underscore the importance of feedback loops and delays (e.g., appeal of facilities growing as more people use them) (42,(51)(52)(53), points in which the systems-consortium also recognised and discussed in regard to implementing a shared strategy. More speci cally, consistent with research, it was recognised that it would take time to build consensus and an develop an effective whole-systems approach (17,25,54,55), but a shared vision would bring in new partners, grow the system, and therefore the extent to which change could be brought about.…”
Section: Discussionmentioning
confidence: 99%